Fenomena Fatherless: Penyebab dan Konsekuensi Terhadap Anak dan Keluarga - Yupi Anesti; Mirna Nur Alia Abdullah (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2024)
Fatherless is a phenomenon which is define as the absence of the father’s role in parenting both physically and psychologically. In married life, disputes and conflicts cannot be avoided so they require trust and commitment to each other. Disputes in family life can have positive impacts, one of which is adjustment to the household environment. However, it cannot be denied that disputes can also threaten the continuity of a marriage, such as divorce. In cases of divorce, fatherless can also appear in children who are victims of divorce. Divorce results in them not being able to feel their father’s presence and his role in accompanying their growth and development. The aim of this research is to describe the fatherless phenomenon and provide an analysis of the fatherless phenomenon regarding family relationships. The research method in this article is to use a descriptive method using literature study data collection techniques. The results of the research show that the phenomenon of fatherlessness can be the cause of parents divorcing, which is due to the lack of the father’s presence in the family so that children experience an absence of figures which can cause conflict in the household and lead to divorce. However, children can also experience fatherlessness after the divorce of their parents, which is due to the lack of time for communication between the child and his father, which indicates the absence of a father figure